2016
DOI: 10.1007/s10714-016-2137-z
|View full text |Cite
|
Sign up to set email alerts
|

Cosmic acceleration from matter–curvature coupling

Abstract: We consider f (R, T ) modified theory of gravity in which, in general, the gravitational Lagrangian is given by an arbitrary function of the Ricci scalar and the trace of the energy-momentum tensor. We indicate that in this type of the theory, the coupling energy-momentum tensor is not conserved. However, we mainly focus on a particular model that matter is minimally coupled to the geometry in the metric formalism and wherein, its coupling energy-momentum tensor is also conserved. We obtain the corresponding R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 80 publications
(84 reference statements)
0
32
0
Order By: Relevance
“…Now, let us compare the above GDE with the corresponding ones in the ΛCDM model and in the minimal coupling model of the f (R, T ) modified gravitational theory, that has been studied in Ref. [14].…”
Section: Geodesic Deviation Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…Now, let us compare the above GDE with the corresponding ones in the ΛCDM model and in the minimal coupling model of the f (R, T ) modified gravitational theory, that has been studied in Ref. [14].…”
Section: Geodesic Deviation Equationmentioning
confidence: 99%
“…We assume that at z = 0, the deviation vector to be zero and its first derivative to be equal to one. We plot the evolution [14]) has been plotted in this figure, so that the results can be compared with our model. We also obtain the observer area-distance in the STM theory as a measurable quantity.…”
Section: Gde For Null Vector Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that observations admit the violation of ordinary energy-momentum conservation law meaning that the energy-momentum sources are nondivergence-free tensors in curved spacetimes [69]. Although this result motivates some physicists to consider the cosmological consequences of this energy conservation violation in f (R,T) gravity [70,71], the idea that the energy-momentum tensor is not conserved in curved spacetime is coming back to Rastall [10]. Recent works in the literature renewed the interest in the Rastall theory [19 -25].…”
Section: Conclusion Remarksmentioning
confidence: 99%
“…Even some gravitational theories have been considered in which the Lagrangian of the geometry, that is usually supposed to be the characteristic of the geometry alone, just from the beginning, and indeed a priori, is presented as a function of the geometry and the matter [97]- [105]. Now, inspiring from these types of ideas and theories, and knowing that, in the Mach ideas, the inertia of a body is not just the intrinsic property of that body, but is caused by the cosmic masses via some interactions (where the influence of the distant bodies preponderates), 17 one can perhaps relate this cause to be due to the cosmic background (e.g., the whole geometry of the universe).…”
mentioning
confidence: 99%